2018
DOI: 10.1016/j.molimm.2018.06.006
|View full text |Cite
|
Sign up to set email alerts
|

Role of complement C5a and histones in septic cardiomyopathy

Abstract: Polymicrobial sepsis (after cecal ligation and puncture, CLP) causes robust complement activation with release of C5a. Many adverse events develop thereafter and will be discussed in this review article. Activation of complement system results in generation of C5a which interacts with its receptors (C5aR1, C5aR2). This leads to a series of harmful events, some of which are connected to the cardiomyopathy of sepsis, resulting in defective action potentials in cardiomyocytes (CMs), activation of the NLRP3 inflam… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

3
32
0
1

Year Published

2018
2018
2023
2023

Publication Types

Select...
7

Relationship

1
6

Authors

Journals

citations
Cited by 34 publications
(36 citation statements)
references
References 154 publications
(236 reference statements)
3
32
0
1
Order By: Relevance
“…C5a reacts with its receptor, leading to cytokine storm, lymphocyte apoptosis, neutrophilic innate immune function loss, cardiomyopathy, disseminated intravascular coagulation, etc. Meanwhile, C5a also affects intracellular calcium homeostasis (Fattahi et al, 2018a;Ward and Fattahi, 2019). SCM is associated with decreased levels of three key enzymes (serca2, NCX, and Na+/K+-atpase) in cardiomyocytes, which are complement receptor-dependent (Fattahi et al, 2018a).…”
Section: The Complement Systemmentioning
confidence: 99%
See 1 more Smart Citation
“…C5a reacts with its receptor, leading to cytokine storm, lymphocyte apoptosis, neutrophilic innate immune function loss, cardiomyopathy, disseminated intravascular coagulation, etc. Meanwhile, C5a also affects intracellular calcium homeostasis (Fattahi et al, 2018a;Ward and Fattahi, 2019). SCM is associated with decreased levels of three key enzymes (serca2, NCX, and Na+/K+-atpase) in cardiomyocytes, which are complement receptor-dependent (Fattahi et al, 2018a).…”
Section: The Complement Systemmentioning
confidence: 99%
“…Meanwhile, C5a also affects intracellular calcium homeostasis (Fattahi et al, 2018a;Ward and Fattahi, 2019). SCM is associated with decreased levels of three key enzymes (serca2, NCX, and Na+/K+-atpase) in cardiomyocytes, which are complement receptor-dependent (Fattahi et al, 2018a). Some studies have suggested that histones may be a target for reducing cardiac dysfunction in sepsis.…”
Section: The Complement Systemmentioning
confidence: 99%
“…Reasons for septic cardiomyopathy could be traced to defects in Na + /K + ‐ATPase, which is critical for effective action potentials in CMs and in other cell types. Defects in sarco/endoplasmic reticulum Ca 2+ ATPase type 2 (SERCA2) and Na + /Ca 2+ (NCX) exchanger led to diastolic buildup of [Ca 2+ ]i in CMs in a manner that was associated with the inability to clear cytosolic [Ca 2+ ]i in CMs during diastole . Such events caused substantial dysfunction and apoptosis of CMs.…”
Section: Molecular Basis Of Cardiac Dysfunction Developing During Polmentioning
confidence: 99%
“…Finally, studies show a link between complement product of C5a and adverse outcomes in septic mice and in septic humans. Use of knockout (KO) mice (lacking C5a receptors; C5aRs) has been shown to protect against adverse events in the heart developing in sepsis . This emphasizes that certain manipulations can be done in septic mice that add important information on how sepsis causes organ dysfunction and might have application in septic humans.…”
Section: Introductionmentioning
confidence: 99%
“…New proposals for the application of fuzzy logic met with great interest of scientific centres, which resulted in creation of many hybrid FMEA methods and models in the fuzzy environment, such as extended MULTIMOORA or AHP, applied e.g. by Fattahi [8] and Hu-Chen [9].…”
Section: Introductionmentioning
confidence: 99%